Tourism and Economic Development in Cultural Festival Based on a Successful Event in Cempluk Village - Eko Prastyo, Redy; Rozuli, Ahmad Imron; Wisadirana, Darsono; Hakim, Muhammad Lukman (Jurnal Aplikasi Manajemen, 2025)
Cultural festivals are vital for sustainable tourism and destination branding, yet many struggle with management inefficiencies. This study examines the relationship between event management, sustainable tourism, and destination branding in Cempluk Village, East Java, Indonesia. This study employs a quantitative approach, collecting primary data through Likert-scale surveys. A total of 200 respondents familiar with tourism in Cempluk Village were selected via incidental and purposive sampling. Validity and reliability tests ensured data accuracy, while multiple regression analysis examined direct and indirect relationships between variables. Findings reveal a significant positive relationship between event management, sustainable tourism, and destination branding. Effective event management enhances sustainable tourism, which, in turn, strengthens destination branding. Additionally, sustainable tourism mediates the impact of event management on destination branding. These insights provide practical implications for policymakers and stakeholders in community-based tourism. Implementing structured event management strategies and sustainability principles can boost local economic growth, cultural preservation, and tourism viability. The study highlights the need for collaborative efforts to optimize cultural festivals as sustainable tourism assets.